Prevalencia de toxocara canis en perros en la ciudad de Huaquillas - Hidalgo Velazquez, Yessenia Matilde (2012)
The gypsy toxocara is a very common parasite in canines that it produces diverse lesions and symptoms. In human the gypsy toxocara is the causal agent of syndromes of varied graveness like larva visceral migrans, larva ocular migrans, neurological toxocarosis and hidden toxocarosis. The objective of this work was to determine the prevalencia of gypsy toxocara in the you take care of Huaquillas, 300 dogs were examined, the used diagnosis technique was for Willis modificate. 61,7% of the samples went positive to Gypsy Toxocara. The positividad percentage in age was of 37,7% in dogs of 0. 1 year of age, 17% in animals from 1 to 3 years and 7% in more animals to 3 years. The prevalence according to the sex was of 33 5 in females and 28,7 in males. As for the race you classifies in Mestizos that gave a percentage of 41% in Mestizos dogs and 20,7% in dogs of another race. In what concerns to the origin the positive percentages they were the following ones: Milton Reyes 14%; The Paradise 12,7%; Ecuador 17,3%; Union Lojana 17,7%; This study demonstrated that the infestación percentage is quite high.